USAGE OF NON-ORTHOGONAL TEMPLATES FOR THE SOLUTION OF THE DIRICHLET PROBLEM FOR THE LAPLACE EQUATION IN THE PLANE - Dudykevych, A. T.; Kardash, A. I.; Levytska, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The Dirichlet boundary problem for the Laplace equation is solved by the finite differences method on non-orthogonal 7-point and 9-point templates. Differencing scheme is built and the algorithm for its implementation is developed.